2006
DOI: 10.1128/mcb.26.10.3728-3737.2006
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Ions Increase Histone H3 Lysine 9 Dimethylation and Induce Transgene Silencing

Abstract: We have previously reported that carcinogenic nickel compounds decreased global histone H4 acetylation and silenced the gpt transgene in G12 Chinese hamster cells. However, the nature of this silencing is still not clear. Here, we report that nickel ion exposure increases global H3K9 mono-and dimethylation, both of which are critical marks for DNA methylation and long-term gene silencing. In contrast to the up-regulation of global H3K9 dimethylation, nickel ions decreased the expression and activity of histone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
187
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(196 citation statements)
references
References 35 publications
6
187
2
1
Order By: Relevance
“…In animal experiments, injection of particulate nickel compounds (nickel sulfide or nickel subsulfide) into mice induced formation of malignant fibrous histiocytomas and sarcomas, with the p16 and Fhit genes often found to be epigenetically silenced in these cancers (9,10). Additional studies have demonstrated that nickel exposure caused truncation of histone H2B and H2A as well as global alterations of a variety of histone modifications, such as histone acetylation, methylation, phosphorylation, and ubiquitination (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). However, the underlying mechanisms responsible for these nickel-induced epigenetic alterations are poorly understood.…”
mentioning
confidence: 99%
“…In animal experiments, injection of particulate nickel compounds (nickel sulfide or nickel subsulfide) into mice induced formation of malignant fibrous histiocytomas and sarcomas, with the p16 and Fhit genes often found to be epigenetically silenced in these cancers (9,10). Additional studies have demonstrated that nickel exposure caused truncation of histone H2B and H2A as well as global alterations of a variety of histone modifications, such as histone acetylation, methylation, phosphorylation, and ubiquitination (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). However, the underlying mechanisms responsible for these nickel-induced epigenetic alterations are poorly understood.…”
mentioning
confidence: 99%
“…Intriguingly, Ni-induced silencing of gpt and increased H3K9me2 levels occurred only when the transgene was integrated near a heterochromatic region (13,14,21). This suggests that Ni could induce H3K9me2 spreading.…”
mentioning
confidence: 94%
“…In the transgenic gpt+ Chinese hamster V79-derived G12 cells, silencing of the bacterial xanthine-guanine phosphoribosyltransferase (gpt) transgene following Ni exposure is associated with an increase in H3K9me2 and a decrease in H3 and H4 acetylation at the promoter and coding regions (13,14,21). Intriguingly, Ni-induced silencing of gpt and increased H3K9me2 levels occurred only when the transgene was integrated near a heterochromatic region (13,14,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have also reported heavy metal-associated histone modifications and chromatin organization [72,73]. Specifically, nickel ions induce the silencing of the gpt transgene in G12 Chinese hamster cells by increasing histone H3K9 dimethylation via inhibition of H3K9 demethylation [73].…”
Section: Heavy Metals-mentioning
confidence: 99%